Inhibitory Effect of Pinealectomy on the Development of Cerebellar Granule Cells in the Chick: A Stereological Study - Tunc, Ayten Turkkani; Aslan, Huseyin; Turgut, Mehmet; Ekici, Fatih; Odaci, Ersan; Kaplan, Süleyman (Elsevier Science BV, 2007)
Melatonin has some effects upon morphological features of various structures in small animals and human being. However, there has been no investigation concerning its physiological role on development of cerebellar granule cells. In this study, the changes induced by pinealectomy procedure on cerebellar development and their granule cell numbers in the chick were investigated using quantitative stereological methods. A total of 15 Hybro Broiler newly hatched chicks were randomly divided into three equal groups: pinealectomy group (n = 5) and non-pinealectomized control group (n = 5) and sham-operated group (n = 5). Pinealectomy procedure and sham operation were done in 3-day-old chicks and all animals were sacrificed for histopathological evaluation and subsequent stereological analysis in the 8th week. Here, it was observed that pinealectomy significantly reduces the granular cell number in cerebellar cortex of the chicks (P < 0.001). The present study is the first stereological study to evaluate the histomorphological effects of pinealectomy on the cerebellar granule cells of the chick. We suggest that the granule cell loss in the cerebellar cortex is due to developmental retardation in early postnatal period, although its exact mechanism is not clear. Based on our findings, we intimate that pineal gland/melatonin might play an important role in the development of cerebellar granule cells in the chick. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Granule Cell; Cerebellum; Chick; Melatonin; Pinealectomy; Stereology